Prevalence of femoroacetabular impingement morphology in asymptomatic youth soccer players: magnetic resonance imaging study with clinical correlation - Anthony Kerbes Yépez; Marcelo Abreu; Bruno Germani; Carlos Roberto Galia (Revista Brasileira de Ortopedia)
Abstract Objective To determine the prevalence of femoroacetabular impingement morphology (FAIM), cam- or pincer-type, by magnetic resonance imaging (MRI) in asymptomatic adolescent soccer players, and to evaluate the possible correlation between alterations on MRI and clinical examination findings. Methods A cross-sectional study was conducted to determine the prevalence of FAIM in asymptomatic youth soccer players aged 13-18 years. A total of 112 hips in 56 players (mean age 15.3 years) were evaluated by MRI. Images were examined by two musculoskeletal radiologists for signs of FAIM. Cam-type (impingement) deformity was diagnosed by alpha angle ≥55° or head-neck offset <7 mm. Pincer-type (impingement) deformity was diagnosed by center-edge angle (CEA) ≥35° or acetabular index ≤0°. Other MRI changes, characteristic of FAIM, were observed. Clinical examination was performed to determine the range of motion (ROM) of the hips. In addition, specific tests for anterolateral and posteroinferior impingement were performed. Results The prevalence of MRI findings consistent with FAIM among this young population was 84.8% (95/112). The alpha angle was ≥55° in 77.7% (87/112) of hips, while the CEA was altered in 10.7% (12/112) of hips. Qualitative MRI findings consistent with FAIM were highly prevalent, and included loss of sphericity of the femoral head (77%), osseous bump (44%), femoral neck edema (21%), and acetabular osteitis (9%). The anterior impingement test was positive in 15% of the hips evaluated. Conclusion Youth soccer players have a high prevalence of FAIM as diagnosed by MRI. There is no correlation between physical examination findings and MRI evidence of FAIM in this population.